Where all light tends to go - Joy, David, 1983- (G. P. Putnam's Sons, 2015)
"Set in North Carolina's Appalachian Mountains, eighteen-year-old Jacob McNeely is torn between appeasing his meth-dealing kingpin father and leaving the mountains forever with the girl he loves"--